Improved methods for the enumeration of heterotrophic bacteria in bottled mineral waters - Ramalho, Rita (2011)
At this time the European Union regulations require that the heterotrophic plate counts (HPC) of mineral waters be assessed at two recovery temperatures: 22°C for 72 h and 37°C for 24 h. This procedure is time consuming and expensive. Development of new rapid methods for microbiological assessment of the microbial flora in the bottled water is an industry-driven need. The objectives of this work were to develop a method for the HPC that utilises only one recovery temperature and one incubation period and evaluate the use of, the LIVE/DEAD® BacLight™ Bacterial Viability Kit, 5-cyano-2,3-ditotyl tetrazolium chloride (CTC) and impedance methods to enumerate viable bacteria in bottled mineral water. Results showed that incubation at 30°C could be used instead of incubation at 22°C and 37°C. Good correlation exists between counts at 30°C and counts at 22°C (r>0.90) and all the pathogens important in mineral water analyses grow similarly at 30°C and 37°C during 24 h. It was demonstrated that impedance methods might be useful to the mineral water industry as a rapid indicator of microbiological quality of the water. Results obtained with BacLight and CTC were similar to those obtained with plate counts.